The Effectiveness of Sule Honey Comsumption in Increasing Milk Production for Working Mothers Using Breastfeeding Pump Method: Efektivitas Konsumsi Sule Honey Terhadap Peningkatan Produksi Asi Bagi Ibu Pekerja Yang Menggunakan Metode Pompa Asi (Mpa) - Baroroh, Ida; Maslikhah (Jurnal Kebidanan Midwiferia, 2021)
Decreasing milk production is a major problem for working mothers to continue breastfeeding their babies after the maternity leave period is over, besides that the lack of support from people around them, especially family, work place, time to pump breast milk, availability of lactation room greatly affects the consistency of milk production. Breastfeeding mothers need help to make the breastfeeding process more successful, namely by consuming foods that can stimulate milk production. An alternative food ingredient to support the nutritional needs of breastfeeding mother is the consumption of soy milk (SULE) and honey. The purpose of this study was to determine the effectiveness of consumption of Sule Honey in increasing breast milk production in worker mothers using the breast pump method. This study used a Quasi Experimental research design with a design used that is the nonequivalent control group design. This study used two groups, namely the treatment group and the control group. The treatment group, namely 20 worker mothers who breastfeed and use breasfeeding method, were given an intervention, namely giving Sule Honey for 2 weeks and recorded on the observation sheet. The control group is 20 worker mothers who breastfeed and use breastfeeding methode who are given health education about the nutritional needs of nursing mothers.